Development of a web-based courseware for secondary schools. - Ng, Peck Suan. (2008)
The aims of this study are: i) to find out how best to use and integrate Web-based technologies into the existing teaching and learning practices at secondary schools, and ii) to develop Web-based courseware on Organic Chemistry.